2016
DOI: 10.4311/2016mb0122
|View full text |Cite
|
Sign up to set email alerts
|

Lack of cave-associated mammals influences the fungal assemblages of insular solution caves in eastern Canada

Abstract: The biogeography of cave fungi and factors that influence community composition are poorly known. The movement of animals into caves from the outside environment is thought to be one factor that affects cave mycota. Islands often have different faunal assemblages from the mainland, and this may affect the fungal diversity of island caves. In 2014 we swabbed walls in three natural solution caves on Anticosti Island, Quebec, to determine the composition of cave fungal assemblages present relative to well-studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Penicillium (9 isolates) was the most apparent genus followed by Clonostachys (5), Fusarium (4), Doratomyces (4), Cephalotrichum (3), Talaromyces (2), Acremonium (2), Xenoacremonium (2), Trichurus (1) and Cladosporium (1). Penicillium [ 4 , 15 , 18 , 21 , 29 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ] and Fusarium [ 4 , 18 , 21 , 29 , 66 , 72 , 74 ] are two of the most reported fungi present in caves. Clonostachys [ 21 , 29 , 68 , 72 , 74 ], Doratomyces [ 21 , 66 , 67 , 68 , 71 , 72 ], Cephalotrichum [ 21 , 29 , 68 , 69 , 74 ], Talaromyces [ 21 , 68 , 69 , 72 , 73 , 74 ], Acremonium [ …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Penicillium (9 isolates) was the most apparent genus followed by Clonostachys (5), Fusarium (4), Doratomyces (4), Cephalotrichum (3), Talaromyces (2), Acremonium (2), Xenoacremonium (2), Trichurus (1) and Cladosporium (1). Penicillium [ 4 , 15 , 18 , 21 , 29 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ] and Fusarium [ 4 , 18 , 21 , 29 , 66 , 72 , 74 ] are two of the most reported fungi present in caves. Clonostachys [ 21 , 29 , 68 , 72 , 74 ], Doratomyces [ 21 , 66 , 67 , 68 , 71 , 72 ], Cephalotrichum [ 21 , 29 , 68 , 69 , 74 ], Talaromyces [ 21 , 68 , 69 , 72 , 73 , 74 ], Acremonium [ …”
Section: Resultsmentioning
confidence: 99%
“…Penicillium [ 4 , 15 , 18 , 21 , 29 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ] and Fusarium [ 4 , 18 , 21 , 29 , 66 , 72 , 74 ] are two of the most reported fungi present in caves. Clonostachys [ 21 , 29 , 68 , 72 , 74 ], Doratomyces [ 21 , 66 , 67 , 68 , 71 , 72 ], Cephalotrichum [ 21 , 29 , 68 , 69 , 74 ], Talaromyces [ 21 , 68 , 69 , 72 , 73 , 74 ], Acremonium [ 15 , 18 , 21 , 29 , 66 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is unlike Glebe Mine, Kitts Cave, and White Cave, where porcupines (Erethizon dorsatum) or beavers (Castor canadensis) introduce significant quantities of organic matter (dung and vegetation) which may increase fungal diversity. In [42], it was found that on Anticosti Island, Quebec, a lack of mammals associated with caves was correlated with the absence of some fungi. Organic matter on the floor of caves may also produce gases that serve as nutrition sources for microbes on cave walls [9].…”
Section: Discussionmentioning
confidence: 99%